Effect of bed particle size on the gas-particle hydrodynamics and wall erosion characteristics in a 550 MWe USC CFB boiler using CPFD simulation. (1st September 2022) - Lee, Byoung-Hwa; Kim, Kang-Min; Bae, Yoon-Ho; Oh, Hyun-Suk; Kim, Gyu-Bo; Jeon, Chung-Hwan; Ahn, Young-Heon
Abstract: To reduce wall erosion in 550 MWe ultra-supercritical (USC) circulating fluidized bed (CFB) boiler, the effect of bed particle size with gas-particle hydrodynamics characteristics is investigated here through computational particle fluid dynamics (CPFD). Most studies on erosion until now have dealt with pilot scale system, but the present study aims to provide valuable information on erosion at full scale in the CFB boiler. The results showed that particle size significantly affected the gas-solid flow in the furnace. Larger particles were difficult to be entrained by the gas stream, which increased the internal circulating rate instead of reducing the external circulation rate. Furthermore, erosion was also influenced by both particle size and circulation rate but did not linearly increase with the particle size. In the cyclone, the erosion rate is highest, which gradually decreases with increasing particle size due to external circulation rate, but the erosion tendency of furnace and other devices are rather highest with the medium-sized particles. As the hydrodynamics and erosion of a USC CFB boiler were studied through CPFD simulation for the first time, the findings of this study may provide considerable insight into and guidance for efficient boiler operation and prevention of shutdown due to erosion. Highlights: CPFD simulation of industrial scale ultra-supercritical boiler is conducted. Effects of particle size on internal/external circulation and erosion are analyzed. Erosion depends mainly on external circulation rate in cyclone. In other devices, erosion shows non-monotonic relationship with particle size.